INOVASI ISI GYOZA DENGAN PROPORSI AYAM DAN IKAN PATIN DENGAN PENAMBAHAN SEMANGGI: UJI SENSORI DAN KESUKAAN - Mulyono, Rizqi; Any Sutiadiningsih; Ita Fatkhur Romadhoni; Asrul Bahar (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to determine the effect of chicken and catfish proportions, as well as the addition of clover leaves, on the sensory characteristics and preference level of gyoza products. The research method used was an experimental design with a factorial approach, and data were analyzed using ANOVA Two-way and Duncan's post hoc test. The results showed that there was a significant interaction effect between the proportion of chicken and catfish and the addition of clover leaves on the sensory attributes of gyoza, particularly in terms of aroma, taste, and overall preference. The best treatment combination was found at a 50% chicken and 50% catfish ratio with 20% clover leaf addition, which received the highest sensory scores. Individually, the chicken and catfish proportion influenced the balance of taste and aroma, with the 50:50 ratio being more preferred than the 60:40 and 70:30 combinations. The addition of 20% clover leaves had a positive contribution in enhancing the aroma and taste without compromising the texture of the product. Panelists' level of preference indicated that the ingredient combination in treatment proportion ayam 50%, patin 50%, dan semanggi 20% has a strong potential to be well received by consumers.